Targeting PAR2-mediated inflammation in osteoarthritis: a comprehensive in vitro evaluation of oleocanthal’s potential as a functional food intervention for chondrocyte protection and anti-inflammatory effects - Patnaik, Rajashree; Varghese, Riah; Jannati, Shirin; Naidoo, Nerissa; Banerjee, Yajnavalka (BMC musculoskeletal disorders, 2024)
Osteoarthritis (OA) is a prevalent degenerative joint disease characterized by chronic inflammation and progressive cartilage degradation, ultimately leading to joint dysfunction and disability. Oleocanthal (OC), a bioactive phenolic compound derived from extra virgin olive oil, has garnered significant attention due to its potent anti-inflammatory properties, which are comparable to those of non-steroidal anti-inflammatory drugs (NSAIDs). This study pioneers the investigation into the effects of OC on the Protease-Activated Receptor-2 (PAR-2) mediated inflammatory pathway in OA, aiming to validate its efficacy as a functional food-based therapeutic intervention. To simulate cartilage tissue in vitro, human bone marrow-derived mesenchymal stem cells (BMSCs) were differentiated into chondrocytes. An inflammatory OA-like environment was induced in these chondrocytes using lipopolysaccharide (LPS) to mimic the pathological conditions of OA. The therapeutic effects of OC were evaluated by treating these inflamed chondrocytes with various concentrations of OC. The study focused on assessing key inflammatory markers, catabolic enzymes, and mitochondrial function to elucidate the protective mechanisms of OC. Mitochondrial function, specifically mitochondrial membrane potential (ΔΨm), was assessed using Rhodamine 123 staining, a fluorescent dye that selectively accumulates in active mitochondria. The integrity of ΔΨm serves as an indicator of mitochondrial and bioenergetic function. Additionally, Western blotting was employed to analyze protein expression levels, while real-time polymerase chain reaction (RT-PCR) was used to quantify gene expression of inflammatory cytokines and catabolic enzymes. Flow cytometry was utilized to measure cell viability and apoptosis, providing a comprehensive evaluation of OC's therapeutic effects on chondrocytes. The results demonstrated that OC significantly downregulated PAR-2 expression in a dose-dependent manner, leading to a substantial reduction in pro-inflammatory cytokines, including TNF-α, IL-1β, and MCP-1. Furthermore, OC attenuated the expression of catabolic markers such as SOX4 and ADAMTS5, which are critically involved in cartilage matrix degradation. Importantly, OC was found to preserve mitochondrial membrane potential (ΔΨm) in chondrocytes subjected to inflammatory stress, as evidenced by Rhodamine 123 staining, indicating a protective effect on cellular bioenergetics. Additionally, OC modulated the Receptor Activator of Nuclear Factor Kappa-Β Ligand (RANKL)/Receptor Activator of Nuclear Factor Kappa-Β (RANK) pathway, suggesting a broader therapeutic action against the multifactorial pathogenesis of OA. This study is the first to elucidate the modulatory effects of OC on the PAR-2 mediated inflammatory pathway in OA, revealing its potential as a multifaceted therapeutic agent that not only mitigates inflammation but also protects cartilage integrity. The preservation of mitochondrial function and modulation of the RANKL/RANK pathway further underscores OC's comprehensive therapeutic potential in counteracting the complex pathogenesis of OA. These findings position OC as a promising candidate for integration into nutritional interventions aimed at managing OA. However, further research is warranted to fully explore OC's therapeutic potential across different stages of OA and its long-term effects in musculoskeletal disorders.